Edukasi dan Pelatihan Bantuan Hidup Dasar pada Sentra Komunikasi Mitra Polri Provinsi Sulawesi Selatan - Nur, Muhammad Purqan; Suarniati, St.; Hasanuddin, Fitria; Ismunandar, Ismunandar (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Indonesia is prone to natural disasters, such as geological and hydrometeorological disasters. This is because the geography, geology, hydrology, climate, and population conditions in Indonesia are prone to disasters caused by non-natural factors such as natural disasters and man-made disasters. Both can cause loss of life, environmental damage, property damage, and psychological impact. This service aims to increase the general community's knowledge of Senkom Mitra Polri, particularly regarding basic life support. The implementation method, namely education using practical modules and training using mannequins, was carried out on February 28, 2023, at the Baitul Ilmi student boarding school building, attended by 30 participants from Gowa Regency and Makassar City. The stages of training implementation consisted of registration of participants, pre-test, provision of material, simulation of basic life support practices by participants one by one with team assistance, post-test, and skills test. This activity involved a doctor with an emergency background providing general material related to basic life support. The results showed that 80% of the trainees understood the material provided. It is hoped that this activity can form a first responder community and increase the role of the community, especially the police partner Senkom in rescuing cardiac arrest patients.